Design and Implementation of Fc Data Forwarding - Xiao, Changfeng; Li, Lin (International Journal of Computer Science and Information Technology, 2024)
In order to meet the increasing data traffic demand of Fiber Channel, a FC data forwarding scheme based on Hardware acceleration technology is proposed. Firstly, an analysis was conducted on existing data forwarding schemes, and it was found that traditional software implementation methods often have performance bottlenecks. Therefore, it is proposed to directly process data forwarding using FPGA and use dedicated hardware modules to achieve high-speed processing of data frames to improve data forwarding speed. On this basis, a high-speed data forwarding scheme based on the FC protocol was designed and a system prototype was implemented. The FC simulation source was used to simulate the airborne environment for data forwarding experiments, which verified the effectiveness and feasibility of the design, significantly improving the speed of FC data forwarding.